Training the "Scaffolding Digital Storytelling" for Secondary Level English Teacher at Middle Aceh - Delfia Herwanis; Rahmanita Zakaria; Erako Gayo (Salus Publica: Journal of Community Service, 2023)
The "Scaffolding Digital Storytelling" training program has undergone a comprehensive evaluation using a rigorous mixed-methods methodology, which includes both quantitative and qualitative assessments. The program demonstrated significant effectiveness in improving participants' comprehension and abilities in digital storytelling and scaffolding. An analysis of assessments conducted before and after training, with the use of statistical tests, revealed a noteworthy enhancement in knowledge and abilities within the experimental group. This underscores the success of the program. The qualitative findings provided more clarity on the participants' experiences, highlighting their active involvement, contentment, and effective incorporation of digital storytelling into their teaching methods. The program's favorable impact on pedagogical techniques was evidenced through observations, surveys, and analysis of lesson plans. The program's revolutionary power was further validated by notable success stories, such as those of HM, LF, and EB, which demonstrated its adaptability across different degrees of technological expertise. The use of digital storytelling in educational settings, as demonstrated by teachers like Sarah Thompson, RM, PK, and BS, highlights the long-lasting beneficial impacts on student involvement, linguistic aptitude, and analytical thinking abilities. Crucially, the program went beyond just one intervention and encouraged educators to continuously improve and adapt. In conclusion, the "Scaffolding Digital Storytelling" training program proves to be a powerful force for promoting positive transformation in both the skills of the participants and the methods of instruction. The significant influence it has on gaining knowledge, effectively incorporating it into teaching methods, and consistently improving student outcomes make it a powerful resource for enhancing language training using digital storytelling and scaffolding strategies.